Studies on Blackening of Canned Prawns 1.Influence of Copper and Iron on Product Blackening - NANDAKUMRAN, M.; CHAUDHUIU, D R.; PILLAI, V. K. (Fishery Technology, 2025)
A linear relationship was observed between the copper content and intensity of blackening in commercially canned prawn meat. Average copper and iron contents of unblackened canned prawn meat were 9.6 and 32.5 ppm on dry weight basis respectively. ln the blackened product copper content ranged from 15.8 to 63.9 ppm and iron content between 43.7 and 71.45 ppm depending on the intensity of blackening. But incorporation of copper in the above raege to experimental cans produced blackening while iron upto 250 ppm did not impart any blackening under standard conditions of canning.